2016
DOI: 10.1038/tpj.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog pathway overexpression in pancreatic cancer is abrogated by new-generation taxoid SB-T-1216

Abstract: The Hedgehog pathway is one of the major driver pathways in pancreatic ductal adenocarcinoma. This study investigated prognostic importance of Hedgehog signaling pathway in pancreatic cancer patients who underwent a radical resection. Tumors and adjacent non-neoplastic pancreatic tissues were obtained from 45 patients with histologically verified pancreatic cancer. The effect of experimental taxane chemotherapy on the expression of Hedgehog pathway was evaluated in vivo using a mouse xenograft model prepared u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Characteristics of the patient cohort are summarized in Table I . The tissue specimen collection and processing, and the data retrieval were as described previously ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of the patient cohort are summarized in Table I . The tissue specimen collection and processing, and the data retrieval were as described previously ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…The high levels of IHH in HAS3-EVs were surprising, given that most of the reported studies on melanoma and other cancers have largely implicated the role of SHH in the process [ 66 68 ]. However, IHH is a well-known stimulus for self-renewal and enhanced proliferation in several cancers, including colorectal [ 69 ], lung [ 70 ], pancreatic [ 71 ], gastric [ 72 ], and T cell acute lymphoblastic leukemia [ 73 ]. Our results also point out that knocking down IHH in MV3-GFP-HAS3 cells negatively impacts the HAS3-EVs ability to enable HA secretion in HaCaT cells and downregulation of HAS2 and HAS3 in MV3 parental cells decreases IHH secretion in EVs.…”
Section: Discussionmentioning
confidence: 99%
“…The cancer stem cell maintenance, tumor-stroma cross-talk, and chemo-resistance could also be affected by interactions between Hedgehog and other signaling pathways. Mohelnikova et al did not found any strong correlation between Hedgehog expression profile and KRAS mutation status in PDAC patients [ 118 ], regardless of previous PDAC studies [ 119 ]. Taxoid involvement with a dysregulated Hedgehog signaling pathway in patients with PDAC could have significant therapeutic benefits.…”
Section: Signaling Pathways Involved In Pcscsmentioning
confidence: 99%
“…Taxoid involvement with a dysregulated Hedgehog signaling pathway in patients with PDAC could have significant therapeutic benefits. New-generation taxoids can abrogate the overexpression of Hedgehog in pancreatic cancer [ 118 ]. Molecular interaction between WNT/β-catenin, Notch, TGF-β, and hedgehog indicates that during oncogenesis, two or more pathways crosstalk with each other.…”
Section: Signaling Pathways Involved In Pcscsmentioning
confidence: 99%